Effect of leadership style and organizational culture on organizational performance - Presilawati, Febyolla; Mirza Tabrani, Abdul Rahman Lubis, Said Musnadi, (Opción, 2019)
The aim of the study is to investigate the effect of leadership style and organizational culture on organizational performance with the organizational environment as variable mediation. The model that will be used in this study is structural equation models or Structural Equation Models (SEM). As a result, the direct effect of organizational culture on the organizational environment is 95.45 percent. In conclusion, the value of Critical Ratio (CR) on the influence of leadership style on the organizational environment where CR> 2.00 and the significance level> 0.05, which means that all variables are influential.